ANALISIS PENDAPATAN PETERNAK AYAM BROILER POLA KEMITRAAN DI DESA BONTOMATENE KECAMATAN MARUSU KABUPATEN MAROS - Iskayani, Veronica Sri Lestari, Wempie Pakiding (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. This research aims to know the revenue earned broiler chicken breeder in Partnership Pattern in Bontomatene village, District Marusu Maros. This research was conducted in March and April 2015 in Bontomatene village, District Marusu Maros. This type of research is quantitative descriptive, which is a type of research that describes the revenue earned broiler chicken breeder in Partnership Pattern in Bontomatene village, District Marusu Maros. The population in this research is the breeders who participated in Partnership Pattern in Bontomatene village, District Marusu Maros as much as 23 breeders, because the population is not too large, then the entire population of the research sample. Analysis of the data used is descriptive statistics. The results obtained by the research that has been done is the revenue earned broiler chicken breeder in partnership pattern Bontomatene village a low of Rp. 1039.67 per head while the highest revenue earned by breeder is Rp. 1423.18 per head.